Oil price forecasting under asymmetric loss - Christian Pierdzioch; Jan-Christoph Rülke; Georg Stadtmann (European University Viadrina, Department of Business Administration and Economics, 2012)
Based on the approach advanced by Elliott et al. (Rev. Ec. Studies. 72, 1197-1125), we found that the loss function of a sample of oil price forecasters is asymmetric in the forecast error. Our findings indicate that the loss oil price forecasters incurred when their forecasts exceeded the price of oil tended to be larger than the loss they incurred when their forecast fell short of the price of oil. Accounting for the asymmetry of the loss function does not necessarily make forecasts look rational.
Keywords: F31; D84; 330; oil price; forecasting; loss function; rationality of forecasts; Ölpreis; Prognoseverfahren; Rationale Erwartung; Verlust; Sachverständige; EU-Staaten